Medium-chain triglycerides combined with DHA improve cognitive function by inhibiting neurocyte apoptosis of the brain in SAMP8 mice - Sun, Yue; Zhou, Dezheng; Wang, Yue; Wang, Zehao; Zhang, Dalong; Qian, Zhiyong; Yan, Jing; Li, Zhenshu; Huang, Guowei; Li, Wen (Experimental gerontology, 2024)
Medium-chain triglycerides (MCTs) and docosahexaenoic acid (DHA, Cn-3, 22:6) are essential in improving cognitive function and protecting neurocytes. This study explored the effects of the combined intervention of MCTs and DHA on inhibiting neurocyte apoptosis of the brain and improving cognitive function in senescence-accelerated mouse-prone 8 (SAMP8). Four-month-old male SAMP8 mice were randomly divided into four treatment groups (12 mice/group): DHA, MCT, DHA + MCT, and control groups, which intervened for seven months. Twelve age-matched male senescence-accelerated mouse resistant 1 (SAMR1) was used as the natural aging group. TUNEL assay and HE staining were used to assess neurocyte apoptosis and damage in the brain of mice. Moreover, the cognitive function was analyzed using the Morris water maze (MWM) and open field (OF) tests. The results showed that the cognitive function of 11-month-old SAMP8 mice decreased with age, and further pathological examination revealed the damaged neurocyte structure, karyopyknosis, cell atrophy, and even apoptosis. MCTs combined with DHA supplementation could increase octanoic acid (C8:0), decanoic acid (C10:0), and DHA levels in the serum, inhibit neurocyte apoptosis, improve neurocyte damage, moreover delay age-related cognitive decline after seven-month treatment. Furthermore, combining MCTs and DHA was significantly more beneficial than MCTs or DHA alone. In conclusion, MCTs combined with DHA could delay cognitive decline by inhibiting neurocyte apoptosis of the brain in SAMP8 mice. •MCTs combined with DHA delayed cognitive decline of SAMP8 mice.•MCTs combined with DHA inhibited neurocyte apoptosis of the brain in SAMP8 mice.•The combination of MCTs and DHA was more beneficial than alone MCTs or DHA.